Non-tuberculous, adenosine deaminase-positive lymphocytic pleural effusion: Consider immunoglobulin G4-related disease - Wand, Ori; Fox, Benjamin D; Shtraichman, Osnat; Moreh-Rahav, Osnat; Kramer, Mordechai R (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Objective: Immunoglobulin G4-related disease (IgG4-RD) is a recently described systemic disorder. Pleural effusion is considered an uncommon manifestation of the disease. We describe a case series of patients with IgG4-RD and clinically significant pleural effusions. Methods: A retrospective analysis of patients with histologically proven IgG4-RD treated for pleural effusion in our clinic. Results: We identified 4 male patients with pleural effusion caused by IgG4-RD. The effusions were lymphocytic exudates, with especially high protein concentrations. All patients had hyperglobulinemia, elevated serum immunoglobulin G (IgG) levels and elevated levels subclasses IgG1 and IgG4. In two patients, levels of adenosine deaminase (ADA) were measured in the effusion and were elevated (309 and 108 IU/L). Tuberculosis was excluded in both cases by pleural biopsy. Involvement of other organs by IgG4-RD was the rule, especially thoracic lymphadenopathy which was prominent in all patients. In all cases, effusion responded to corticosteroids therapy. One patient developed radiological findings compatible with rounded atelectasis during remission. Conclusions: IgG4-RD may cause an ADA-positive, lymphocytic exudate with a high protein concentration, characteristics resembling tuberculous effusion. Thoracic lymphadenopathy, hyperglobulinemia, and an increased total IgG, IgG1, IgG4 may suggest the diagnosis. Not previously described, IgG4-RD pleural inflammation may result in rounded atelectasis.